A critical perspective on generative AI and learning futures. An interview with Stefan Popenici (Journal of Applied Learning and Teaching, 2023)
We present a wide-ranging interview with Stefan Popenici, a distinguished scholar and public speaker with extensive experience in higher education. Popenici's research focuses on the impact of artificial intelligence (AI) on teaching, learning, quality assurance, and student engagement in higher education. The interview delves into the themes of his book, Artificial Intelligence and learning futures: Critical narratives of technology and imagination in higher education (2023), exploring the intersection of AI, intelligence, and societal issues such as eugenics and racism. Popenici critiques the power of tech titans and the belief in technology as a panacea, especially in higher education. The discussion also addresses the identity crisis in higher education, the potential of revisiting Humboldt's 19th-century vision of the university, and the challenges and opportunities presented by the AI revolution. Popenici's insights into the role of AI in assessment, graduate and academic employment, and the future of academic work are particularly illuminating. The interview concludes with Popenici's reflections on his own educational journey and future plans.